Nurses’ Attitude toward Medication Errors in Al-Hilla Teaching Hospitals - Aljesham, Amenah Abd Al Hassan Jebur; Shimran, Hasanain Yhiya (Journal of Science in Medicine and Life, 2025)
Background: Medication errors are a common occurrence in healthcare settings, contributing significantly to needless patient harm. Nurses play a critical role in medicine management and serve as the final line of defense against errors. Their views on medical mistakes have an impact on error identification, prevention, and reporting, all of which are critical for patient safety. In developing nations, including Iraq, low resources, heavy workloads, and weak protection mechanisms face additional obstacles. Objective: This study aims to analyze nurses' attitudes and perceptions regarding medication mistakes in Al-Hilla Teaching Hospitals, identify socio-demographic and employment variables, and explore barriers to error reporting. Methods: A quantitative descriptive cross-sectional design was employed. The study sample included 170 nurses from critical care units of Al-Hilla and Al-Imam Al-Sadiq Teaching Hospitals, selected via purposive sampling. Data were collected using a validated questionnaire (reliability r = 0.82) covering demographics, perception, and attitudes toward medication errors and reporting. Responses were scored on a 3-point Likert scale (agree = 3, neutral = 2, disagree = 1). Data analysis involved descriptive statistics, including frequencies, percentages, means, and standard deviations. Results: Most participants were female (57.6%), aged 20–30 years (75.9%), and held a bachelor’s degree (52.4%). The mean score for perception of medication errors was 2.70 (SD = 0.506), and the mean attitude toward reporting errors was 2.48 (SD = 0.657), indicating generally positive views. However, nurses identified fear of punishment, heavy workload, insufficient managerial support, and limited training as barriers to reporting. Less-experienced nurses were particularly affected. Conclusion: Nurses at Al-Hilla Teaching Hospitals demonstrate positive attitudes toward medication errors, but organizational and cultural barriers limit consistent reporting. Implementing non-punitive policies, supportive supervision, continuous training, and accessible reporting systems is recommended to enhance patient safety and promote a culture of transparency.